Modern Islamic Historiography Analysis of Guided Democracy Political Islam - Azmi, Fikri Aly (Indonesian Journal of Islamic Studies, 2026)
General Background: Islamic historiography in Indonesia has undergone significant transformation alongside the emergence of academically trained historians adopting critical and interdisciplinary approaches. Specific Background: One prominent contribution is Ahmad Syafii Maarif’s work Islam dan Politik: Teori Belah Bambu Masa Demokrasi Terpimpin (1959–1965), originally his master’s thesis, which examines Islamic political parties during the Guided Democracy era. Knowledge Gap: Despite its pioneering nature, limited scholarly reassessment has critically examined the scope, balance, and analytical depth of this work within modern Islamic historiography. Aims: This study aims to revisit Maarif’s work through literature review and descriptive analysis to evaluate its historiographical contribution and limitations. Results: The findings indicate that the work provides an early and significant analysis of Islamic political party activities during Guided Democracy, particularly highlighting the strategies of the NU Party, but it disproportionately emphasizes NU while underrepresenting other parties such as PSII and Perti. Novelty: This study offers a focused historiographical critique that situates Maarif’s work within the broader development of modern Islamic historiography in Indonesia. Implications: The study underscores the need for more balanced and comprehensive historiographical analyses of Islamic political movements, encouraging further critical engagement and methodological rigor in the study of Indonesian Islamic history. Highlights: Early scholarly examination of Muslim political organizations during 1959–1965 is identified. Disproportionate attention is given to Nahdlatul Ulama compared to other groups. Limited analytical coverage of PSII and Perti creates gaps in historical interpretation. Keywords: Historiography, Guided Democracy, Ahmad Syafii Maarif